Human Resource for Climate Change Response Policy Implementation in Ho Chi Minh City: Situation and Solutions - Son, Ngo Hoai; Hoa, Nguyen Van (VNU Journal of Science: Policy and Management Studies; Vol 35 No 4DO - 10.25073/2588-1116/vnupam.4190, 2019)
Being severely affected by climate change, Ho Chi Minh City needs to focus on developing human resource for its climate change response policy. This is because human resource is a key factor for a successful response. This paper uses secondary data from the Department of Natural Resources and Environment of Ho Chi Minh City to analyze the current situation of the city’s two main groups of human resources for climate change: a  core group and a complementary group. The data show that, although the core group is highly qualified, it lacks staff with deep expertise in policy and climate change. As for the complementary group, the city has not focused on training it in both short and long terms. In order to improve the effectiveness of climate change response in the coming years, Ho Chi Minh City needs to implement at least three solutions: (01) recruiting additional staff with expertise in policies and climate change; (02) promoting training for the core personnel; and (03) building and implementing both short and long-term training plans for complementary staff.